RANCANG BANGUN WEBSITE BADAN PENGAWAS PEMILIHAN UMUM (BAWASLU) KALIMANTAN TENGAH - Ade Chandra Saputra; Agus Sehatman Saragih (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2019)
The misuse of digital image images is increasing, data or information that is of a personal nature can easily be known by others who are not entitled through digital images. This can cause material and immaterial losses to people whose personal information is misused by others. Then the application applies the Rijndael algorithm to secure digital image images which contain information or data that is of a personal nature. In securing digital image images, Rijndael's algorithm is used to protect the information contained in the image, the algorithm runs with processes such as SubBytes, ShiftRows, MixColumns, and AddRoundKey. The methodology applied is data collection methods such as field studies and literature studies, then Waterfall software development methods (Communication, Planning, Modeling, Construction, and Deployment) for system design